Comparison on biodegradation of low-density polyethylene (LDPE) mixed with corn starch by A. Niger, R. Oryzae and their biofilm / Nazatul Nabila Mohamad ... [et al.] - Mohamad, Nazatul Nabila; Razali, Zainab; Sarip, Muhammad Naiman; Kamaruddin, Sharir Aizat; Abdullah, Shafinas; A Hamid, Huzaifah; Ahmad Nasir, Nor Atikah Husna (Universiti Teknologi MARA Cawangan Pahang, 2021)
This research focusses on the degradation of Low-density polyethylene (LDPE) mixed with corn starch by A. niger, R. oryzae and their biofilm. The biofilm was formed using 96 well plates before being observed using Scanning Electron Microscopy (SEM). The mycelial mass was observed in the SEM image of the biofilm indicating the present of both species. The rate of degradation of A. niger, R. oryzae and their biofilm were evaluated based on weight loss within 7 days of incubation time and further analyzed using Fourier Transform Infrared Spectroscopy (FTIR). Based on the comparison, the biofilm of A. niger and R. oryzae has shown higher degradation compared to the fungi alone (without the biofilm), up to 1.87%. In addition, amylase and cellulase enzymes were secreted by the biofilm to accelerate the degradation. Through the FTIR analysis, it was found that there are differences in the polymer structure after 7 weeks of fermentation compared to LDPE control. The bond formation differences before and after fermentation were observed with the changing in carbonyl and ester structures suggesting enzymes secreted by the biofilm had possibly changed the original polymeric structure of the LDPE. Thus, it can be concluded that the biofilm of A.niger and R.oryzae could be a breakthrough in providing a solution in bioplastic degradation.